The European Union and new dimensions of citizenship - Postigo-Asenjo, Marta (My University, 2016)
The European integration process raises interesting challenges to the conceptualization and the exercise of citizenship in a multinational cosmopolitan context. Certainly, the current institutional architecture of the European Union (EU) faces tough criticism. On the one hand, anti-European parties and Euro-skeptics, by means of Euro-exit initiatives and on nationalist grounds, challenge the very existence of the European integration project. On the other hand, federalist and pro-European intellectuals often complain that the EU has not gone far enough with respect to the democratic, the civic and/or the social integration of the Union. In spite of such criticism, the European integration process has given rise to a novel and singular form of citizenship: the so-called dual form of citizenship. The European dual form of citizenship entails a combination of national and supranational civic membership. EU citizenship –which is automatically conferred on every EU citizen by the Treaty on the Functioning of the EU–, does not replace, but complements national citizenship. In this regard, it implies the automatic expansion and improvement of citizens’ rights and opportunities –for example, the right to vote and stand as a candidate in municipal and European Parliament elections and the right to move and reside freely within the EU–. Moreover, EU treaties (now including the Chapter of Fundamental Rights of the EU, legally binding on the supranational institutions and on national governments since 1 December 2009) and institutions such as the Court of Justice of the European Union, contribute to the enhancement of the legal and judicial mechanisms for the protection of basic rights. In spite of these benefits and achievements, the democratic shortcomings of the EU’s decision-making architecture encourage citizens’ distrust of the EU. In addition, one basic goal and achievement of the European integration project, which is citizens’ mobility within the EU, is facing serious setbacks. Indeed, the Schengen Agreements allow for exceptions which are too easily employed by the member states in order strengthen their borders controls and restrict intra-European mobility; which has just intensified as a consequence of the economic crisis, and more recently, the “refugees crisis”. The focus of my paper is on the conceptual challenge that the European integration project raises to the modern idea of citizenship. One of the basic conditions for the exercise of the democratic citizenship has traditionally been national membership. Yet, this has just been challenged by the European integration process and the dual form of citizenship that it has guaranteed. In Section 08, of the ECPR General Conference, I would like to address the conceptual implications of EU citizenship.
Keywords: Ciudadanía; Unión Europea; Citizenship; Cosmopolitanism; European Union; Nation-state